149 Outcomes and Complications in Patients With Uncontrolled Diabetes Undergoing Cervical Spine Surgery. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Skovrlj, Branko; Guzman, Javier Zabdi; Hecht, Andrew; Qureshi, Sheeraz; Cho, Samuel K.
Abstract: INTRODUCTION: Diabetes mellitus (DM) is a highly prevalent systemic disease that has been shown to increase morbidity and mortality after spine surgery. A few studies have demonstrated negative effects on DM patients who undergo cervical spine procedures, but whether uncontrolled DM influences surgical outcome is still unknown. METHODS: The National Inpatient Sample was queried from 2002 to 2011. Patients who underwent cervical spine surgery for degenerative conditions were identified using the International Classification of Diseases, Ninth Revision, Clinical Modification codes. χ 2 test was used for analysis of categorical data and Student t test was used for continuous variables. Multivariable analysis was done to see if uncontrolled diabetes was an independent risk factor for inpatient mortality. RESULTS: A total of 10 532 patients with uncontrolled DM underwent cervical spine surgery from 2002 to 2011. Patients with uncontrolled DM were more likely to be older (60.2 vs 52.4 years for no DM, P < .0001) and of male sex (54.1% vs 48.8, P < .0001). There was a significant increase in the prevalence of postoperative cardiac (2.1-fold), respiratory (3.7-fold) and genitourinary (2.2-fold) complications in uncontrolled DM patients. Also, higher prevalence of deep venous thrombosis (5.6-fold), pulmonary embolism (4.6-fold) and postoperative infection (4.7-fold) were observed. Mean length of stay was extended by nearly 5 days (7 days vs 2.3 days, P < .0001) and hospital costs increased by 80% ($25 146 for uncontrolled DM vs $14 162 for no DM, P < .0001). Mortality rate was significantly higher as well (1.1% for uncontrolled DM vs 0.17% with no DM, P < .0001). When controlling for age, race, sex, insurance, procedure types and hospital characteristics (eg, bed size, location, teaching vs nonteaching) in multivariable analysis, uncontrolled DM was a significant factor increasing the odds of inpatient mortality (odds ratio = 2.6; 95% confidence interval = 1.5-4.5, P = .0005). CONCLUSION: Patients undergoing degenerative cervical spine procedures with uncontrolled DM had significantly increased rates of major acute perioperative complications. Length of stay and costs were also higher. There was a 6.4-fold increase in mortality rate, and uncontrolled DM increases the likelihood of inpatient mortality.